2014
DOI: 10.1007/s11103-014-0275-9
|View full text |Cite
|
Sign up to set email alerts
|

Rice phenylalanine ammonia-lyase gene OsPAL4 is associated with broad spectrum disease resistance

Abstract: Most agronomically important traits, including resistance against pathogens, are governed by quantitative trait loci (QTL). QTL-mediated resistance shows promise of being effective and long-lasting against diverse pathogens. Identification of genes controlling QTL-based disease resistance contributes to breeding for cultivars that exhibit high and stable resistance. Several defense response genes have been successfully used as good predictors and contributors to QTL-based resistance against several devastating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
124
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(133 citation statements)
references
References 94 publications
1
124
0
Order By: Relevance
“…Phenylalanine ammonia lyase (EC 4.3.1.24) is a key enzyme in the phenylpropanoid pathway of higher plants involved in the production of several compounds like lignins, coumarins and flavonoids that are related to plant defense (La Camera et al 2004). Several studies have reported the induction of the PAL gene in response to fungal elicitors and its association with enhanced fungal defense (Pellegrini et al 1994; Shadle et al 2003; Tonnessen et al 2015). Interestingly, the wheat PAL gene had highly similar orthologs in several other plants indicating that it is conserved across species as observed by Rawal et al (2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Phenylalanine ammonia lyase (EC 4.3.1.24) is a key enzyme in the phenylpropanoid pathway of higher plants involved in the production of several compounds like lignins, coumarins and flavonoids that are related to plant defense (La Camera et al 2004). Several studies have reported the induction of the PAL gene in response to fungal elicitors and its association with enhanced fungal defense (Pellegrini et al 1994; Shadle et al 2003; Tonnessen et al 2015). Interestingly, the wheat PAL gene had highly similar orthologs in several other plants indicating that it is conserved across species as observed by Rawal et al (2013).…”
Section: Discussionmentioning
confidence: 99%
“…Plant defensins are cysteine-rich peptides involved in plant innate immunity that are generally active against a broad spectrum of fungal pathogens and other microbes (Broekaert et al 1995; de Carvalho and Gomes 2009). While the PAL gene has been discussed earlier, Tonnessen et al (2015) reported a rice PAL gene ( OsPAL4 ) that was associated with broad spectrum disease resistance. Finally, the ABCG transporter family (also pleiotropic drug resistance family) members are also known to be involved in plant defense (Stukkens et al 2005; Stein et al 2006; Krattinger et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…PAL is also involved in the synthesis of phytoalexins and lignin to prevent cell wall penetration by the pathogen. Tonnessen et al (2015) reported that OsPAL4 and possibly OsPAL6 were key contributors to resistance governed by QTL and were potential breeding targets for improved broad-spectrum disease resistance in rice. The expression of PAL6 was up-regulated in the Pi21 -RNAi line relative to Nip as early as 24 hpi.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, an earlier (2 dpi) and stronger (6-to 8-fold) activation of OsPAL4 and OsPAL6 was observed. OsPAL4 and to a lesser extent OsPAL6 were shown to be key elements in resistance to several bacterial and fungal diseases governed by QTL (Tonnessen et al, 2015). Inhibition of PAL activity by AOPP application to TOG5681 led to increased gall formation, although this inhibition could not fully restore susceptibility.…”
Section: Role Of Hormonal Pathways Is Complexmentioning
confidence: 99%